Aggregation of plaque disclosing agent in a dentifrice Incorporação de evidenciador de placa bacteriana a um dentifrício - Débora Dias da Silva; Camila da Silva Gonçalo; Maria da Luz Rosário de Sousa; Ronaldo Seichi Wada (University of São Paulo, 2004)
Dental plaque removal is an important issue in health promotion. Toothbrushing is one of the main methods employed for such purpose, since it can prevent dental caries by means of the fluoride present in the dentifrice. Dentifrices might contain plaque disclosing agents and thus allow dental plaque observation. The aim of this study was to assess whether utilization of a plaque disclosing agent interfered with plaque removal among adolescents, as well as the difference between utilization of erythrosine tablets and dentifrices containing plaque disclosing agent. The sample was composed of 62 students from Piracicaba, SP, Brazil, aged 12 to 14 years old, divided into 3 groups: G1 or control group (toothbrushing without plaque disclosure); G2 (plaque disclosing with an erythrosine tablet and toothbrushing) and G3 (toothbrushing with dentifrice containing plaque disclosing agent). After toothbrushing, disclosure of the remaining dental plaque was performed in all groups with a fuchsin tablet and measured through the Simplified Oral Health Assessment Index (OHI-S), in two stages with a 2-month interval between them. The analysis of variance (ANOVA) showed that there was no difference in the OHI-S index between the groups (p>0.05), however the G3 displayed a higher proportion of students with plaque reduction (23%) than G2 (21%), besides the smallest difference in the mean remaining dental plaque. There was no difference between groups; however, it was suggested that the dentifrice with plaque disclosing agent had positive results in relation to the erythrosine tablet, even though the small sample size may have interfered with the results, indicating the need of complementary studies. Na promoção de saúde, a remoção da placa bacteriana é um fator importante e um dos métodos que incentivam sua remoção, é a escovação dentária, podendo-se prevenir a cárie dental através do íon flúor dos dentifrícios. Estes podem conter evidenciadores, possibilitando a visualização da placa bacteriana. Assim, avaliou-se o uso de evidenciadores na remoção de placa bacteriana em adolescentes, e se houve diferença entre pastilhas de eritrosina e dentifrício contendo evidenciador. A amostra foi de 62 escolares de Piracicaba- SP, entre 12 e 14 anos, dividida em 3 grupos: o G1 como grupo controle (escovação dental sem prévia evidenciação de placa); o G2 (evidenciação de placa com pastilha de eritrosina e escovação dental) e o G3 (escovação com dentifrício contendo evidenciador de placa). Após a escovação, evidenciou-se a placa remanescente com pastilha de fucsina nos 3 grupos, medida pelo Índice de Higiene Oral Simplificado (IHOS), sendo realizada em 2 fases, com intervalo de 2 meses. Segundo a Análise de Variância (ANOVA), não houve diferença no índice IHOS entre os grupos (p>0,05). Entretanto, o G3 apresentou maior proporção de escolares onde houve diminuição do IHOS (23%) em relação ao G2 (21%) e menor diferença nas médias de acúmulo de placa. Não houve diferença entre os grupos, entretanto, sugere-se que o dentifrício com evidenciador de placa tenha resultados positivos em relação à pastilha de eritrosina, apesar da amostra ter sido pequena e poder ter interferido, havendo necessidade deste resultado ser melhor explorado.